2008
DOI: 10.1364/oe.16.007720
|View full text |Cite
|
Sign up to set email alerts
|

High responsivity GaNAsSb p-i-n photodetectors at 13µm grown by radio-frequency nitrogen plasma-assisted molecular beam epitaxy

Abstract: GaNAsSb/GaAs p-i-n photo notdetectors with an intrinsic GaNAsSb photoabsorption layer grown at 350 degrees C, 400 degrees C, 440 degrees C and 480 degrees C, have been prepared using radio-frequency nitrogen plasma-assisted molecular beam epitaxy in conjunction with a valved antimony cracker source. The i-GaNAsSb photoabsorption layer contains 3.3% of nitrogen and 8% of antimony, resulting in DC photo-response up to wavelengths of 1350 nm. The device with i-GaNAsSb layer grown at 350 degrees C exhibits extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recently, a conversion efficiency of 44% was reported for a triple junction solar cell including a bottom junction based on GaInNAs(Sb) grown by molecular beam epitaxy (MBE) [3]. Adding antimony to ternary GaAsN to form GaAsNSb compounds can be also used to lower the bandgap beyond the 1-eV limit, serving as an alternative to quinary alloys, which are somewhat more difficult to grow due to the presence of three elements of group V [4,5]. The drawback in using dilute nitrides/antimonides is related to challenges in material fabrication [6] and formation of defects [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a conversion efficiency of 44% was reported for a triple junction solar cell including a bottom junction based on GaInNAs(Sb) grown by molecular beam epitaxy (MBE) [3]. Adding antimony to ternary GaAsN to form GaAsNSb compounds can be also used to lower the bandgap beyond the 1-eV limit, serving as an alternative to quinary alloys, which are somewhat more difficult to grow due to the presence of three elements of group V [4,5]. The drawback in using dilute nitrides/antimonides is related to challenges in material fabrication [6] and formation of defects [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…GaNAsSb was firstly proposed by Ungaro et al [7] as a potential GaAs-based small bandgap (o1.4 eV) material. Recently, GaNAsSb has been demonstrated as a promising material for near infrared photodetectors [8][9][10] and photoconductive switches [11] due to its capability to achieve small energy bandgap, E g (0.8-1.0 eV), and to be lattice-matched to a GaAs substrate. These characteristics enable GaNAsSb to be a potential active material for the 1 eV photovoltaic junction.…”
Section: Introductionmentioning
confidence: 99%
“…The used well width of non-doped (i-i-i) SQWs is equal to 4.4 Â 10 4 cm À 3 . Experimentally, Tan et al [16] have examined the absorption in GaNAsSb/GaAs p-i-n photodetectors at the wavelength 1.3 mm, and they found that the absorption coefficient is estimated to be 1.3 Â 10 4 cm À 1 . Furthermore, we have found that the absorption coefficient magnitude at T e h On the other hand, the increase of the absorption coefficient versus the n doping density is observed in the study of CdS/ZnSe QWs and [27] and InGaN/GaN vertical blue LEDs structures [31].…”
Section: Resultsmentioning
confidence: 99%
“…They found that the photoluminescence peak energy for GaN y As 1 À x À y Bi x is more temperature insensitive than the band gap of In 1 À x Ga x As y P 1 À y . Moreover, quantum wells (QWs) based on dilute nitride such as GaInNAs/ GaAs [15] and GaNAsSb/GaAs [16] are highly involved for the design of light-emitting diodes (LEDs) and photodetectors. Moreover, we have studied in a previous work [17] the electronic band structure of non-doped lattice-matched GaN x As 1 À x À y Bi y /GaAs QWs operating at 1.3 and 1.55 mm using BAC model.…”
Section: Introductionmentioning
confidence: 99%